Mimicking Myelodysplastic Syndrome: Importance of Differential Diagnosis - Luo, Thomas; Zurko, Joanna; Astle, John; Shah, Nirav N. (Case Reports in Hematology, 2021)
Copper deficiency is a rare nutritional deficiency with hematological manifestations that mimic those found in myelodysplastic syndrome, a hematological malignancy incurable without allogeneic hematopoietic stem cell transplantation. Bone marrow biopsy findings and peripheral blood counts are oftentimes insufficient to differentiate the two conditions. Moreover, the symptoms of copper deficiency can arise years after the surgery, making diagnosis a challenge. In patients with new-onset pancytopenia, copper deficiency must be considered on the differential, especially in the setting of known risk factors such as bariatric surgery, zinc supplementation, and celiac disease. Herein, we present a case of a 61-year-old female with a remote history of gastric bypass being evaluated for MDS in the context of progressive pancytopenia and new-onset paresthesias. The patient was found to have low serum copper and ceruloplasmin. Copper supplementation largely resolved the hematological abnormalities, but the limb paresthesias remain. This case highlights the need to identify copper deficiency early and distinguish it from MDS in order to prevent permanent neurological deficits and catastrophic response should the patient undergo hematopoietic stem cell transplantation.